New Mysida (Crustacea) in the genus Pseudomma from the Bellingshausen Sea (Southern Ocean) - San Vicente, Carlos (Zootaxa, 2011)
Two new Erythropinae mysids, Pseudomma bellingshausensis and P. melandi are described from specimens sampled with a suprabenthic sled in the Bellingshausen Sea (Southern Ocean). P. bellingshausensis and P. melandi are distinguishable from its closest congeners, P. antarcticum Zimmer, 1914, P. jasi Meland & Brattegard, 1995 and P. islandicum Meland & Brattegard, 2007 by ocular plate sculpturing and telson armature. A key for the Antarctic and Subantarctic Pseudomma species is also included.